2002
DOI: 10.1007/s701-002-8279-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Arteriovenous Malformations with Hemorrhage

Abstract: The patient had a high risk of hemorrhage. Adding hemodynamic stress to this situation, hemorrhage would have been expected to occur at an early time after the initial intervention for hemorrhagic AVM. Considering the risk of hemorrhage, other AVMs should undergo surgery as soon as possible after resection of hemorrhagic AVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
(42 reference statements)
0
4
1
1
Order By: Relevance
“…Multiple AVMs are rare, except in the Rendu-Osler-Weber and Wyburn-Mason syndromes, with an incidence in major series ranging from only 0.3 to 4%. 2,4,10,13,14,16 Iizuka, et al, 4 divided multiple AVMs into two groups: congenital or acquired. According to their classification, the multiple AVMs presented here should be classified as acquired lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple AVMs are rare, except in the Rendu-Osler-Weber and Wyburn-Mason syndromes, with an incidence in major series ranging from only 0.3 to 4%. 2,4,10,13,14,16 Iizuka, et al, 4 divided multiple AVMs into two groups: congenital or acquired. According to their classification, the multiple AVMs presented here should be classified as acquired lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This structural instability in nidi and other vulnerable areas of the cerebral vasculature may result from hemodynamic changes following partial obliteration of nidi, which has been frequently hypothesized throughout the literature [6,19,26,30,31,32,33,34]. It has been observed that obliteration of a nidus may be associated with subsequent alterations in blood pressure and flow [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of multiple AVM surgery, secondary hemorrhage has occasionally been noted after the first operation, and hemodynamic changes during the different treatment stages have demonstrated previously undiagnosed vascular malformations. 2,4,7,8) Utsuki et al and Tada et al emphasized such a event, 6,7) and Salcman et al and de Sousa et al recommend total resection of all lesions; first ruptured AVM, and then the remaining lesions. 1,5) In the present case, angiography demonstrated a small tectal AVM after resection of an AVM in the occipital lobe, so the angiographical appearance of the lesion might have been affected by thrombosis of the shunt just after hemorrhage, by absorption of the hematoma, and by hemodynamic changes after resection of the larger AVM.…”
Section: Discussionmentioning
confidence: 99%
“…5) Multiple AVMs differ somewhat from common solitary AVMs in terms of clinical course and surgical strategy, because of the influence of hemodynamic changes during resection of multiple lesions. 6,7) We present a case of multiple AVMs in which initial angiography revealed only solitary AVM; however, after removal of the first AVM, repeat angiography disclosed another AVM that was the true cause of hemorrhage. To the best of our knowledge, this is the first such case to be reported, and this situation would appear extremely rare.…”
Section: Introductionmentioning
confidence: 95%